Mitochondrial displacement loop region single nucleotide polymorphisms and mitochondrial DNA copy number associated with risk of ankylosing spondylitis - Zhang, Jingjing; Peng, Chenxing; Xu, Shuo; Zhao, Yufei; Zhang, Xiaoyun; Zhang, Shasha; Guo, Zhanjun (International journal of rheumatic diseases, 2023)
AimThe pathogenesis of ankylosing spondylitis (AS) seems to be associated with genetics, the environment, heredity, and oxidative stress. Single nucleotide polymorphisms (SNPs) in the displacement loop (D‐loop) region of mitochondrial DNA (mtDNA) and mtDNA copy number were investigated for their correlation with AS patients.MethodsThis study included 83 AS patients and 100 healthy controls from the Second Hospital of Hebei Medical University. DNAs were extracted from blood samples for polymerase chain reaction analysis and quantitative real‐time polymerase chain reaction analysis. Plasma reactive oxygen species (ROS) levels were measured by fluorescent probe technology.ResultsThe distribution frequencies of the minor alleles of nucleotides 16304C (p = .037), 16311C (p = .027), and 152C (p = .034) were remarkably higher in AS patients than in healthy controls, which indicated that the16304C, 16311C, and 152C alleles were correlated with an increased risk of AS. Simultaneously, mtDNA copy number was statistically higher in patients with AS compared with controls (1.450 ± 0.876 versus 0.835 ± 0.626, p < .001). We also observed an increased ROS generation in AS patients compared with controls (27 066.169 ± 18 364.819 versus 14 758.330 ± 5854.946, p < .001) subsequently. In addition, the AS susceptible SNP 16311C is associated with high ROS levels (35 065.177 ± 26 999.934 vs. 25 005.818 ± 14 999.495, p = .043).ConclusionOur study demonstrated that SNPs in the mtDNA D‐loop could be AS risk biomarkers with the potential to promote oxidative stress levels; mtDNA copy number‐induced mitochondrial dysfunction may also be involved in AS pathogenesis.